Financing the orderly transition to a low carbon economy in the EU: the regulatory framework for the banking channel - María J. Nieto; Chryssa Papathanassiou (Journal of Banking Regulation, 2023)
Among the largest economies of the world, the EU not only has set the most ambitious and legally binding objectives for the reduction of the GHG emissions but also it has accompanied these objectives with a "state of the art" regulatory framework in the realms of investor protection and safety and soundness. Our paper focuses on the bank financing channel and highlights regulatory areas for improvement. To mobilize the necessary funds worldwide, a degree of interoperability of regional taxonomies is required, which calls for international cross-pollination and coordination to mitigate financial risks and the risk of harmful market fragmentation (BCBS 2022, FSB 2022). Also, the full interoperability between the international and the EU corporate reporting standards is a desirable objective. A building bloc methodological approach would make such interoperability easier having the sustainability impact perspective of the "double materiality objective" as an additional layer of the international requirements well understood to all investors in EU undertakings. As per the inclusion of climate risks in prudential regulation, it is completed for Pillar 3 disclosures relating effectively with the EU Taxonomy. Climate risk's long-term horizon still needs to be implemented in Pillar 2 by linking bank transition plans with stress testing based on climate risk scenario analysis covering both transition and physical risk. The inclusion of climate risks in Pillar 1 faces challenges similar to those of supervisors internationally. Fostering global ambition is an explicit objective of the EU. Its leadership on the realms of investor protection and prudential regulation of climate risks should ideally inform international cooperation and impregnate international standards. This will secure that investments for the fulfillment of the EU climate objectives will flow from in and outside the EU.
Keywords: G21; K23; O38; 330; ESG; Climate risk; Banking supervision